Protein turnover and proteolysis during sporulation of Bacillus subtilis - Sekar, V; Hageman, J H (Folia microbiologica, 1987)
A two-dimensional electrophoretic method was used to show that protein degradation occurs immediately after the end of exponential growth but that its occurrence is masked in the usual assay methods for a 2-h period and that degradation is apparently nonselective with respect to protein molar mass or charge. The results suggest that considerable reutilization of internal amino acids may occur during sporulation regardless of the size of the external chase. Finally, the levels of intracellular proteinase activities present even at the end of exponential phase growth, as measured in vitro, are sufficient to account for the maximum rates of protein degradation observed in vivo.
Keywords: Molecular Weight; elektroforéza v polyakrylamidovém gelu; isoelektrická fokusace; Mathematics; leucin; molekulová hmotnost; koncentrace vodíkových iontů; matematika; Leucine; Endopeptidases; endopeptidasy; Bacillus subtilis; Bacterial Proteins; Electrophoresis, Polyacrylamide Gel; spory bakteriální; Hydrogen-Ion Concentration; Isoelectric Focusing; Spores, Bacterial; bakteriální proteiny